P0789SERUM URIC ACID IS ASSOCIATED WITH CHRONIC KIDNEY DISEASE PROGRESSION AND MORTALITY: INSIGHTS FROM THE CKD-REIN COHORT. (6th June 2020) - Prezelin-Reydit, Mathilde; Combe, Christian; Harambat, Jerome; Massy, Ziad; Metzger, Marie; Lange, Céline; Lambert, Oriane; Stengel, Benedicte; Leffondré, Karen
Abstract: Background and Aims: The association between hyperuricemia and CKD progression is not well established in Europe and, to our knowledge, has not yet been investigated using longitudinal measurements. Method: We used data from CKD-REIN, a prospective cohort study conducted in 40 representative French nephrology clinics, which included 3033 patients with CKD stages 3 to 5 between 2013 and 2016. Patients who had no serum uric acid or no creatinine measure at within 6 months of their inclusion date in the CKD-REIN study were excluded. All uric acid measures were taken into account, from inclusion to the occurrence of renal replacement therapy (RRT), death, or end of follow-up, whichever came first. We used a shared random-effect model for the joint analysis of individual trajectories of uric acid and the hazard of the composite outcome (RRT or death before RRT) and each specific event separately. Hazard ratio were adjusted (aHR) for age, sex, primary kidney disease, metabolic syndrome, cardiovascular disease, proteinuria (< 30, 30-300, > 300 mg/day), and the CKD-EPI estimated glomerular filtration rate (eGFR) at baseline. In a sensitivity analysis, we further adjusted for individual eGFR trajectory. Results: A total of 2781 patients (65.5% men, median age 69 years) were included. At baseline, the median eGFR was 31.8 mL/min/1.73m2 and the median uric acid value was 425 µmol/L. During a median follow-up of 3.2 years, 434 patients received RRT and 264 died before RRT. At any time of follow-up, an increase of 100 µmol/l of the current value of uric acid was associated with a 16% increased hazard of RRT or death before RRT (aHR 1.16, 95% CI 1.07-1.26). The estimated effect of uric acid was similar with RRT (aHR 1.18, 95% CI 1.04-1.34) and death before RRT (aHR 1.16, 95% CI 1.05-1.28). When further adjusted for eGFR trajectory, the estimated effect of uric acid on the composite outcome was much weaker (aHR 1.06, 95% CI 0.98-1.16). Conclusion: A higher current level of uric acid is associated with a strong increase in the hazard of RRT or death before RRT in European patients with CKD stage 3 to 5. However, the association is much weaker after adjustment for eGFR trajectory. Further analyses are necessary to better understand the dynamic of the association between uric acid and GFR.